Peningkatan Efektivitas Pelayanan Surat Menyurat Dengan Chatbot Sebagai Media Untuk Mengurangi Antrian di Kantor Desa Mekarmukti Cikarang Utara - Wiji Safitri; Nasrun Baldah; Pupung Purnamasari (BADAN PENERBIT STIEPARI PRESS, 2024)
Good service is queue-free. As a field related to operational management, many methods are used to reduce or even eliminate queues. Technology is one method used to eliminate queues. Mekarmukti Village, as a village with a large population, needs to use technology in mail services to eliminate queues. The aim of this community service is to implement WhatsApp Chatbot to increase efficiency in correspondence services thereby reducing queues in Mekarmukti Village. The method used in the service is training and practice in creating WhatsApp Chatbots. The service was carried out in Mekarmukti Village, North Cikarang. Chatbot training and practice participants are Mekarmukti Village officials related to services and correspondence. After carrying out training and practice in creating WhatsApp chatbots, queues were reduced in the service section. Apart from that, the public can access correspondence information within 24 hours via WhatsApp Chatbot. By carrying out this service, it is hoped that it will be able to reduce queues for sending correspondence.